Veil: The Secret Wars of the CIA 1981-1987 - Bob Woodward (New York Simon & Schuster, 1987)
From Bob Woodward, legendary investigative reporter, Veil is the story of the covert wars that were waged by the CIA across Central America, Iran and Libya in a secretive atmosphere and became the centerpieces and eventual time bombs of American foreign policy in the 1980s. With unprecedented access to the government's highest-level operators, Woodward recounts one of the most clandestine operations in US nation's history.
Keywords: History; Nonfiction; Politics